PERFORMANCE ANALYSIS OF UMTS NETWORKS AS REFERENCE OF SIGNAL INTERFERENCE HANDLING - Rahmad Hidayat (Universitas Trunojoyo Madura, 2018)
A network, not apart from the existence of the maintenance process, not least in the telecommunications network. In the maintenance of telecommunication networks, especially 3G -UMTS network, it is necessary to report on UMTS network performance in the previous days. The purpose of this study is to conduct a study of network performance reports in the previous days to help the UMTS network maintainers in analyzing and determining corrective measures in the area in trouble. The results of this study indicate that the RTWP method is helpful in deciding whether NodeB is affected by interference at the maximum acceptance signal threshold of -92dBm / cell. The resulting report resumes can be used as reference of areas where signal interference is occurring for improvement in the area in which the signal interference is occurring.